A meta-analysis of interindividual differences in innovation. (September 2019) - Amici, Federica; Widdig, Anja; Lehmann, Julia; Majolo, Bonaventura
Abstract : The ability to innovate and the social transmission of innovations have played a central role in human evolution. However, innovation is also crucial for other animals, by allowing them to cope with novel socioecological challenges. Although innovation plays such a central role in animals' lives, we still do not know the conditions required for innovative behaviour to emerge. Here, we focused on interindividual differences in innovation by (1) extensively reviewing existing literature on innovative behaviour in animals and (2) quantitatively testing the different evolutionary hypotheses that have been proposed to explain interindividual variation in innovation propensity during foraging tasks. We ran a series of phylogenetically controlled mixed-effects meta-regression models to determine which hypotheses (if any) are supported by currently available empirical studies. Our analyses show that innovation is more common in individuals that are older and belong to the larger sex, but also in more neophilic and/or explorative individuals. Moreover, these effects change depending on the study setting (i.e. wild versus captive). Our results provide no clear support to the excess of energy or the bad competitor hypotheses and suggest that study setting and interindividual differences in traits related to personality are also important predictors of innovation. Highlights: We review previous studies on innovation across nonhuman taxa. We conduct a meta-analysis to assess interindividual differences in innovation. More neophilic, more explorative or older individuals innovate more. Individuals of the larger sex also innovate more. These effects differ in captive and wild animals.